Microbiome Composition and Its Impact on the Development of Allergic Diseases - Peroni, Diego G.; Nuzzi, Giulia; Trambusti, Irene; Di Cicco, Maria Elisa; Comberiati, Pasquale (Frontiers in Immunology, 2020)
Allergic diseases, such as food allergy (FA), atopic dermatitis (AD), and asthma, are heterogeneous inflammatory immune-mediated disorders that currently constitute a public health issue in many developed countries worldwide. The significant increase in the prevalence of allergic diseases reported over the last few years has closely paralleled substantial environmental changes both on a macro and micro scale, which have led to reduced microbial exposure in early life and perturbation of the human microbiome composition. Increasing evidence shows that early life interactions between the human microbiome and the immune cells play a pivotal role in the development of the immune system. Therefore, the process of early colonization by a “healthy” microbiome is emerging as a key determinant of life-long health. In stark contrast, the perturbation of such a process, which results in changes in the host-microbiome biodiversity and metabolic activities, has been associated with greater susceptibility to immune-mediated disorders later in life, including allergic diseases. Here, we outline recent findings on the potential contribution of the microbiome in the gastrointestinal tract, skin, and airways to the development of FA, AD, and asthma. Furthermore, we address how the modulation of the microbiome composition in these different body districts could be a potential strategy for the prevention and treatment of allergic diseases.